Optimized Synthesis of New Thiosemicarbazide Derivatives with Tuberculostatic Activity - Corina Popovici (MDPI AG, 2021)
Original results are presented in the field of research that addresses the extension of the reaction of residue of acyl-thiosemicarbazide fixation on the structure of 5-nitrobenzimidazole by a sulphonic group. The aim of the study is the increase of new thiosemicarbazide derivatives’ applicative potential in the field of biochemistry, with a wide range of medical applications. The newly obtained compounds were characterized by using elemental analysis and spectral analysis (FT-IR and 1H NMR). A study regarding the optimization of the chemical reactions was made. The performed in vitro biological tests confirmed the tuberculostatic activity of three newly obtained compounds against Mycobacterium tuberculosis.